Dupilumab with concomitant topical corticosteroid treatment in adults with atopic dermatitis with an inadequate response or intolerance to ciclosporin A or when this treatment is medically inadvisable: a placebo‐controlled, randomized phase III clinical trial (LIBERTY AD CAFÉ). (1st May 2018) - de Bruin‐Weller, M.; Thaçi, D.; Smith, C.H.; Reich, K.; Cork, M.J.; Radin, A.; Zhang, Q.; Akinlade, B.; Gadkari, A.; Eckert, L.; Hultsch, T.; Chen, Z.; et al.
Summary: Atopic dermatitis (also called AD or eczema) is a chronic skin disease found in up to 1 in 10 adults, causing itchy rashes that may cover most of the body. Ciclosporin, an oral treatment (taken by mouth) commonly used for AD, doesn't always work and can have significant side effects. Other broadly‐acting oral medications are sometimes used, but not approved, for AD. Dupilumab is a new medication approved in many countries for adults with inadequately controlled moderate‐to‐severe AD. Dupilumab specifically targets pathways in the body that drive AD. Researchers in Europe evaluated how well dupilumab injections improved rashes, itch, and daily lives of people whose AD required ciclosporin, but for whom ciclosporin wasn't working or caused intolerable side effects, or whose medical conditions prevented its use. Among 325 participants, 110 received 300 mg dupilumab once‐weekly, 107 received it every two weeks, and 108 received placebo (dummy drug) once‐weekly. All participants used topical (applied to the skin) corticosteroids during the 16‐week study. Dupilumab improved AD rashes: at Week 0, participants' Eczema Area and Severity Index (EASI) scores were about 31 (scale: 0–72), but by Week 16, 59% to 62% of dupilumab‐treated participants achieved 75% or greater improvement in EASI, versus 29.6% of people on placebo. Dupilumab also improved itch, other symptoms, mood, and quality of life. Conjunctivitis and injection‐site reactions were more frequent among dupilumab‐treated patients; skin infections (excluding herpes) and AD exacerbations (worsening) were more frequent with placebo. The authors conclude that dupilumab plus topical corticosteroids significantly improved AD even in adults with AD who had previously failed treatment with or were unable to use ciclosporin.